Elite control through marriage over institutional change - Francis D. Kim; Prateek Raj (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2025)
Economic inequality remains a persistent and widely studied issue in the social sciences. South Korea provides a striking example where the top 23 business groups, controlled by ultra-wealthy, family-owned conglomerates (chaebols), have maintained significant economic persistence and resisted outsider entry, even amidst the disruptive forces of the 21st-century digital age. This study sheds light on how chaebol families have strategically evolved their use of marriage alliances as a key channel to political networks, significantly shaping the dynamics of elite influence over time. In the pre-democratic era, chaebols often formed marriages with politicians to strengthen their influence and boost corporate value. For example, the 2024 divorce between SK Group's Chey Tae-won and Roh So-young, daughter of former President Roh Tae-woo, highlights how such alliances helped secure key advantages, like SK's telecom permit in the 1980s (BBC News, 2024.5). However, marriages with other elites or commoners didn't provide the same benefits. Contrary to the perspective presented by The Economist (2015.4) that such practices among Korean chaebols are enduring, this study finds that blood-based alliances between politicians and elite businessmen was a temporal, institution-specific strategy that have largely disappeared in the democratic era. As South Korea transitioned to a more liberalized regime, the frequency of these political marriages has drastically declined, as confirmed by our analysis. Instead, chaebol families have adapted by leveraging elite marriages within their own business circles to sustain family control over top business groups. These practices have ensured their continued economic dominance while limiting outsider entry into their exclusive networks. This study documents the evolution of marriage alliances as a critical mechanism through which chaebols have navigated changing institutional landscapes, maintaining their entrenched economic power despite shifting political and social conditions.
Keywords: 330